Development and validation of an interprofessional collaborative educational module on the self-management of foot for individuals with type II diabetes mellitus in India [version 4; peer review: 2 approved, 1 approved with reservations] - Gagana Karkada; Sushma Prabhath; Ciraj Ali Mohammed; Arun G. Maiya; Harihara Prakash Ramanathan; M Ganesh Kamath; Ganesh Handady (F1000Research)
Background Insufficient awareness of foot self-care among diabetic individuals results in diabetic foot ulcers especially in the Indian population considering its varied ethnicity and lifestyle practices. The management of diabetes and diabetic foot ulcers therefore demands a well-coordinated approach that involves multiple healthcare providers (HCPs). The present study aims to develop and validate an interprofessional collaborative (IPC) educational program involving HCPs to efficiently oversee and instruct the public on appropriate strategies for self-managing diabetic foot health in the Indian population. Methods The research group worked on creating an educational module titled ‘An Interprofessional Collaborative Educational Module on Self-Management of Foot for Individuals with Type II Diabetes Mellitus.’ The objective of this module was to promote the adoption of proper practices in self-managing foot health for individuals with type 2 diabetes mellitus. A panel of 13 experts participated in a two-stage validation process using the Delphi method to assess the module and its educational resources. Subsequently, the module was tested on a group of 30 participants, i.e., individuals with diabetes, with its efficacy evaluated through conversation analysis and in-depth interviews. Results The three-month-long module included three sessions 1: Diabetes and its health implications 2: Diabetic foot and self-management 3: Interprofessional education in diabetic foot care The mode of content delivery was via Whatsapp, and the educational resources, in the form of pamphlets, flowcharts, handouts, case-based cartoons, and videos on diabetes, including diabetic foot, its risks, and self-management, were shared regularly. All participating experts consensually validated the module and educational resources. Analysis of in-depth interviews revealed that the module immensely benefitted the participants and helped them improve their knowledge and practices of foot care in diabetes. Conclusions The study highlights the importance of developing and validating IPC educational modules tailored to diabetic foot care. It can aid in enhancing adherence to proper diabetic foot care practices.